2018
DOI: 10.18517/ijaseit.8.6.6692
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Afghanistan’s Cyber Security Incident Response Team

Abstract: Persistent cyber threats require effective and efficient mitigation techniques. The cyber security incident response team (CSIRT) is expected to respond to external and internal cyber threats or incidents. Various organizational, national, and international level CSIRTs have been developed for defending and protecting such kinds of threats. Developing countries like Afghanistan have also formed a Computer Emergency Response Team for handling national cyber incidents although it provides limited services to onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The phases are preparation, discovery, containment, investigation, remediation, prevention, and lessons learned (Adamov & Carlsson, 2016). The incident lifecycle presented identification and declaration, analysis, response, and lessons learned phases (Jalal et al, 2018). Al-Dhaqm et al (2020) suggested the incident phases include pre-incident response, incident response, and post-incident response.…”
Section: Cyber Incident Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The phases are preparation, discovery, containment, investigation, remediation, prevention, and lessons learned (Adamov & Carlsson, 2016). The incident lifecycle presented identification and declaration, analysis, response, and lessons learned phases (Jalal et al, 2018). Al-Dhaqm et al (2020) suggested the incident phases include pre-incident response, incident response, and post-incident response.…”
Section: Cyber Incident Responsementioning
confidence: 99%
“…There were several similarities and differences between the academic literature and the perspectives of ecommerce industry fraud experts. The literature review identified an incident response model that included preparation, discovery, containment, analysis, response, and improvement phases (Adamov & Carlsson, 2016;Al-Dhaqm et al, 2020;Jalal et al, 2018;Lamis, 2010;Pilitsky et al, 2021;Pinto & Talley, 2006;Rollason-Reese, 2003;Ruefle et al, 2014;Sadik et al, 2020,). The five cyber incident phases of the empirical model were similar the literature model's preparation, discovery, analysis, response, and improvement phases.…”
Section: Processesmentioning
confidence: 99%
“…However, less-developed countries have fewer funding alternatives when compared to developed ones (Skierka and Hohmann, 2015). For these countries, some alternative options include government sponsorship, fee-based services, in-kind supports, or a combination of these could be funding alternatives for national CSIRTs (Jalal et al, 2018). Likewise, in lowincome countries, the availability of qualified staff or solid technology pipeline, training options, external support, and cultural differences create greater challenges due to limited critical infrastructure, lower living standards, underdeveloped industrial base, and low HDI.…”
Section: The Need For National Csirts In Low-income Countriesmentioning
confidence: 99%